The Initial Impact of Organization Development Intervention on Transformational Servant-Type Leadership and Organizational Effectiveness in the 21st Century: A Case Study of an International Christian Humanitarian Organization - Aumpradithpun, Nuchanath; Villavicencio, Ed.D, Salvacion E (ABAC ODI JOURNAL Vision. Action. Outcome, 2014)
The main purpose of this action research is to investigate the impact of organization development intervention (ODI) on leadership style and performance of the organization in terms of organizational effectiveness that has implemented the principles advocated by transformational servant-type model. Toward that end, a new emphasis on a healthy, effective, holistic, and learning organization that nurtures and magnifies the best in human beings is developed. In this study, the action research was conducted with a pair of main variables, which were transformational servant-type leadership and sustainable organizational effectiveness. Planned action research model and Whole Brain Literacy (WBL) model were used as the organization development (OD) tools to determine the correlation between these two variables. A sample of 144 managers and executive of Non-Profit International (NPI) was selected as sub-population that was representative of the total population. To explore the empirical relationships between the constructs, both qualitative and quantitative measurements were used for data triangulation. The research instruments consisted of the electronic web-based questionnaire for the pre-and post-ODI survey assessments and the structured interviews and direct observations. Quantitative data obtained from the questionnaires in relation to the hypotheses was analyzed using regression analysis to estimate the relationships among variables. Qualitative data from interviews and observations were also analyzed using a combination of content analysis and a four-perspective WBL analysis research instrument. The study revealed that planned ODI, especially with the use WBL model, had significant impact on transformational servant-type leadership practices and organizational functioning. However, quantitative findings indicated some weak statistical relationships between some of the sub dimensions under transformational servant-type leadership and those under organizational effectiveness. Nonetheless, overall there was evidence of positive impact following the implementation of ODI. A set of recommendations was proposed for further research like extending the action research to other organizations, either in the same or other industries and cultures which will make the research become more conclusive. Further application of OD theoretical concepts to execute change process through OD activities can be carried out in NPI with the aim to capitalize on the focal system’s Christian identity, values, and unique employer brand. KEY WORDS: Action research, Whole Brain Literacy, transformational and servant-type leadership, sustainable organizational effectiveness, performance.